A conceptual study to explore the critical drivers for the successful cloud computing with special reference to customer relationship management in Indian MSMEs. (1st January 2013) - Mehta, Arpita; Suriyanarayanan, J.
This review research focuses on Indian MSMEs, who represent a significant proportion of MSMEs in the world and their unique character of business practice, driven by Indian culture, has substantial impacts on their attitude toward CRM implementation, adoption and usage. The methodology adopted in undertaking the study was basically conceptual review and literature survey along with the comparative analysis. Relevant literature is discussed to identify the relationship between these issues. Finally, based on thorough literature review and conceptual analysis a list of critical drivers was outlined for the successful customer relationship management in Indian MSMEs so that one can manage the cloud computing and customer relationship management (CRM), efficiently and effectively. Besides, the scope for further research has also been included in this paper. The paper would be of interest to the policy makers, entrepreneurs, consultants, industry experts and research students.